2010
DOI: 10.1007/s00421-010-1738-6
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte membrane fluidity and indices of plasmatic oxidative damage after acute physical exercise in humans

Abstract: Optimal levels of membrane fluidity are essential for numerous cell functions including cell growth, solute transport and signal transduction. Since exercise enhances free radical production, our aim was to evaluate in healthy male subjects the effects of an acute bout of maximal and submaximal exercise on the erythrocyte membrane fluidity and its possible relation to the oxidative damage overproduction due to exercise. Subjects (n = 34) performed three cycloergometric tests: a continuous progressive exercise,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…The plasma membrane is highly sensitive to the surrounding physical and chemical environment, leading to the proposal that the plasma membrane is the primary detector of stress stimuli and activator of the cellular stress response (48). Subsequently, recent studies suggest that the plasma membrane is central in mediating the cellular stress response and aiding in cellular tolerance to a variety of stressors, including osmotic (34), temperature (44), and oxidative stress (3). This study provides additional evidence for the membrane-sensing model, as we show for the first time that a physical stressor rapidly fluidizes plasma membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma membrane is highly sensitive to the surrounding physical and chemical environment, leading to the proposal that the plasma membrane is the primary detector of stress stimuli and activator of the cellular stress response (48). Subsequently, recent studies suggest that the plasma membrane is central in mediating the cellular stress response and aiding in cellular tolerance to a variety of stressors, including osmotic (34), temperature (44), and oxidative stress (3). This study provides additional evidence for the membrane-sensing model, as we show for the first time that a physical stressor rapidly fluidizes plasma membranes.…”
Section: Discussionmentioning
confidence: 99%
“…[4,5,7] In the studies of Zuk et al, it was also found out that an increase in the erythrocyte elastic modulus worsens the ability of a cell to bind oxygen and transport it through capillaries. [1,7,15] It is known that blood cells suspended in plasma or physiological salt solution (erythrocytes, platelets and leukocytes) carry a negative charge at their physiological pH, which ensures their normal functioning. [10,16] In our studies, the value of the surface potential of the erythrocyte membrane on the 30 th day of adaptation in the blood of chickens in group 2 was 51% higher than the values in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…It gives an objective assessment of the physiological state of the organism and predicts the development of an adaptation process in changing environmental conditions. [1][2][3][4] The parameters of the erythrocyte geometry characterize the properties of red cells to deform under external impact and to change the viscous properties of blood, which largely determines the quality of capillary blood flow and indicates a certain change in the rheological properties of the blood. [1,[5][6][7] In this regard, the study of structural and metabolic status of red blood cells of chickens when adapting to production factors is not only of scientific but also of practical interest.…”
mentioning
confidence: 99%
“…Increased oxidative stress has been linked to a shortening of life span [2]. Several studies report alterations in the erythrocyte membrane during human aging [4,5].…”
Section: Introductionmentioning
confidence: 99%